The Moderating Role of BAZNAS Policy in the Relationship Between Service Quality, Attitude Toward Wealth, and the Intention to Pay Zakat in Indonesia - Yusrizal; Muh Zilal Hamzah; Hilman Latief; Natris Idriyani; Sutarman (Journal of Economics and Management, 2026)
Zakat represents a cornerstone of Islamic socio-economic justice, functioning both as a religious obligation and a public instrument for redistributing wealth. Despite Indonesia's status as the world's most populous Muslim-majority nation, the country faces a persistent gap between its zakat potential and actual zakat collection. This paper investigates the determinants of zakat intention, specifically service quality and attitude toward wealth, while introducing BAZNAS policy as a moderating variable. The study is grounded in the Theory of Planned Behavior (TPB) and public policy argumentation theory, and uses a quantitative approach involving 800 muzakki respondents. SmartPLS 4 was used to analyze relationships among constructs and test moderation effects. The results show that both service quality and attitude toward wealth have significant positive effects on the intention to pay zakat. More importantly, the presence of strong BAZNAS policy moderates and strengthens these effects. The implication is that internal motivations do not solely drive religious behavior but are also shaped by institutional environments. This paper makes theoretical contributions by extending TPB with an institutional moderation dimension and practical contributions by offering a framework for refining zakat policy. The study highlights the need for policymakers to enhance service standards and design zakat policies that build public trust and engagement.